The “causes” and the “motives” in the emigration of Brazilians to France - Ribeiro de Almeida, Gisele Maria (2000)
International migration has become one eminent contemporary subject of research, there are several analysis aimed at explaining and analyzing the increasing spatial mobility of population in the world. This paper reflects on the conditions that engender such intense mobility, but without losing the complexity of the migration process, like as pointed out by Sassen (1993), the flows are made by “persons”. If there are structural processes operating in these conditions that promoter migration, there are also specific dimensions that enable it (Bogus, 1995a). In this sense, we will discuss here the theoretical resources available to a sociological understanding of migration, recognizing its structural causes (SINGER, 1973) - associated with conditions in the origin and destination - and at the same time considering the importance of selectivity of the migration (Lee, 1980). In order to understand contemporary international flows, Portes (1999) argues that in general these originate in the peripheral countries and are intended to developed countries, especially for those whom there are historical links or for countries that creates expectations of consumption that can not be satisfied in native country. However, in the case of the flow Brazil-France, the relations between these two countries are more tenuous – if we compared to other countries, for example, the U.S. or Japan – and that increasing the weight of the selectivity of this migration, then one research on the topic requires a guiding hypotheses to explained it.